2013
DOI: 10.1126/science.1230374
|View full text |Cite
|
Sign up to set email alerts
|

Topology of Feather Melanocyte Progenitor Niche Allows Complex Pigment Patterns to Emerge

Abstract: Color patterns of bird plumage affect animal behavior and speciation. Diverse patterns are present in different species and within the individual. Here we study the cellular and molecular basis of feather pigment pattern formation. Melanocyte progenitors are distributed as a horizontal ring in the proximal follicle, sending melanocytes vertically up into the epithelial cylinder which gradually emerges as feathers grow. Different pigment patterns form by modulating the presence, arrangement, or differentiation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
125
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(131 citation statements)
references
References 36 publications
5
125
0
Order By: Relevance
“…Melanin is the most common component of colouration in animals; it is synthesised in melanocytes and deposited as granules in various organs [14]. Different pigment patterns form by modulating the presence, arrangement, or differentiation of melanocytes [21]. Therefore, melanin-based pigmentation is associated with a series of functional genes.…”
Section: Discussionmentioning
confidence: 99%
“…Melanin is the most common component of colouration in animals; it is synthesised in melanocytes and deposited as granules in various organs [14]. Different pigment patterns form by modulating the presence, arrangement, or differentiation of melanocytes [21]. Therefore, melanin-based pigmentation is associated with a series of functional genes.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in adult chicken, ASIP expression is found only adjacent to pheomelanin or apigmented areas [2,4]. In contrast with these studies, our system comprised controlled stages of embryogenesis in a wild-type phenotype and we found that ASIP was distributed throughout the feather pulp, but only on the ventrum (Fig 4Ai).…”
Section: Discussionmentioning
confidence: 78%
“…Previous studies emphasized a role of inhibition of MC1R for within-feather pattern formation [2,4,21]. For example, in adult chicken, ASIP expression is found only adjacent to pheomelanin or apigmented areas [2,4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Color patterns are prominent features of many animals and play important roles in camouflage, shoaling, mate choice, the perception of threatening behavior, or the protection against UV irradiation (Protas and Patel, 2008;Howe et al, 2013;Lin et al, 2013). Pigment phenotypes in fish are more complicated than in amniota.…”
Section: Introductionmentioning
confidence: 99%